PENERAPAN MODEL PROBLEM BASED INTRUCTIONS (PBI) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 023 KERUBUNG JAYA KECAMATAN BATANG CENAKU - Siti Fatonah; Otang Kurniaman; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The background of this research is the facts that occurred in the fourth SDN 023 Kerubung Jaya, who showed symptoms of the students did not master the material science lessons have been learned. The problem of this research is "Is the Problem Based model application intructions (PBI) can improve learning outcomes science subjects Grade IV SDN 023 Kerubung Jaya KacamatanBatang Cenaku?". The purpose of this research to improve learning outcomes of science subjects Grade IV through the application of the model Problem Based Intructions (PBI) in SDN 023 Kerubung Jaya subdistrict Batang Cenaku Indragiri Hulu. This study took place in the fourth grade SDN 023 Kerubung Jaya and held on March 22 until April 1, 2016 with the number of subjects as many as 25 people consisting of 14 male students and 11 female students. This research is a classroom action research conducted in two cycles. Based on the results the percentage increase learning outcomes in basic score, an average of 61.4 increased in Deuteronomy Daily I became 75, with the increase of 22.14%. In Deuteronomy Daily II increased to 81.4 with an increase of 8.5%. An overall increase of 30.63%. So we can conclude the implementation of the model Problem Based Intructions (PBI) can improve learning outcomes IPA fourth grade students of SD Negeri 023 Kerubung Jaya subdistrict Batang Cenaku second semester of academic year 2015/2016. Keywords: Problem Based Model Intructions, Learning Outcomes, IPA